Prophylaxis in people with haemophilia - Coppola, Antonio; Franchini, Massimo; Tagliaferri, Annarita (Thrombosis and Haemostasis, 2009)
A four-decade clinical experience and recent evidence from randomised controlled studies definitively recognised primary prophylaxis, i.e. the regular infusion of factor concentrates started after the first haemarthrosis and/or before the age of two years, as the first-choice treatment in children with severe haemophilia. The available data clearly show that preventing bleeding since an early age enables to avoid or reduce the clinical impact of muscle-skeletal impairment from haemophilic arthropathy and the related consequences in psycho-social development and quality of life of these patients. In this respect, the aim of secondary prophylaxis, defined as regular long-term treatment started after the age of two years or after two or more joint bleeds, is to avoid (or delay) the progression of arthropathy. The clinical benefits of secondary prophylaxis have been less extensively studied, especially in adolescents and adults; also in the latter better outcomes and quality of life for earlier treatment have been reported. This review summarises evidence from literature and current clinical strategies for prophylactic treatment in patients with severe haemophilia, also focusing on challenges and open issues (optimal regimen and implementation, duration of treatment, long-term adherence and outcomes, cost-benefit ratios) in this setting.
Keywords: Prophylaxis; bleeding; children; haemophilia; quality of life